2008
DOI: 10.1073/pnas.0703015105
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in tracking the long-term global trend in tropical forest area

Abstract: The long-term trend in tropical forest area receives less scrutiny than the tropical deforestation rate. We show that constructing a reliable trend is difficult and evidence for decline is unclear, within the limits of errors involved in making global estimates. A time series for all tropical forest area, using data from Forest Resources Assessments (FRAs) of the United Nations Food and Agriculture Organization, is dominated by three successively corrected declining trends. Inconsistencies between these trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
263
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(270 citation statements)
references
References 48 publications
2
263
0
5
Order By: Relevance
“…Thus, the quality of data, estimations and level of precision are quite different among them (Hansen et al 2013). For the countries only using RS surveys, some variables such as the forest area change, growing stock or biomass are sometimes difficult to estimate, particularly if there is no field assessment and precision estimates are rarely available (Grainger 2008;Romijn et al 2015).…”
Section: The Forest Resources Assessmentmentioning
confidence: 99%
“…Thus, the quality of data, estimations and level of precision are quite different among them (Hansen et al 2013). For the countries only using RS surveys, some variables such as the forest area change, growing stock or biomass are sometimes difficult to estimate, particularly if there is no field assessment and precision estimates are rarely available (Grainger 2008;Romijn et al 2015).…”
Section: The Forest Resources Assessmentmentioning
confidence: 99%
“…In his analysis of global forest trends using the Food and Agriculture Organization's Forest Resource Assessment data set, Grainger (2008) has identified forest regrowth as an important source of uncertainty. Using the Republic of Panama as a model country, Pelletier et al (2011) further showed that a poor understanding of land-use dynamics, which are related to the agriculture-fallow cycle or shifting cultivation, may induce up to 20% error in reference emission levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding the causes of deforestation has been challenging, in part because multiple ecological, political, economic and social factors can all be influential and interact over a vast range of spatial scales 13 . These difficulties are exacerbated by limited knowledge about the pattern and extent of deforestation 14,15 . We have some insight into the forces that influence tree cover dynamics at national scales [16][17][18] , and within local landscapes 19,20 , but little research has attempted to bridge this scale gap.…”
mentioning
confidence: 99%